Oy Mama - Ben-Dor, Orna; Maiman, Noa (Israel, 2009)
Holocaust-survivor Fira has adopted a small Israeli-born girl – a child uprooted, just as Fira was. The adoption is Fira's token of gratitude for her own rescue: she survived the Holocaust thanks to a Polish woman who hid her family from the Nazis. The portrait of an elderly lady becomes not only a journey through the twentieth century, but also a parable on the humanity that shines through in the most adverse of circumstances.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films